(untitled) (Research, Society and Development, 2022)
This study focuses on discussing the post-return care of spontaneous circulation used in patients with Cardiopulmonary arrest. The object of the article: To analyze what are the procedures to be applied in the care of a patient with cardiorespiratory arrest; Investigate what care should be applied to a patient with post-return of spontaneous circulation. The methodology used to support the work was the narrative review. Conclusion: the procedures to be applied in the care of a patient with CPA involve Basic Life Support (BLS) and Advanced Life Support (ALS). The care to be taken during the care of a patient after the return of spontaneous circulation as a result of a CRA, in addition to the BLS and ALS, are: the stages of immediate or early attention, recovery and rehabilitation and the performance of physical evaluations, neurophysiological, cognitive and psychosocial, to detect sequelae. It is also recommended to carry out tests such as Cranial Tomography, Magnetic Resonance Imaging and a Magnetic Resonance Spectroscopy and Positron Emission Tomography (PET), to check for brain injuries. In addition, other care is recommended, such as optimized ventilatory, hemodynamic, neurological and metabolic support and Therapeutic Hypothermia (TH).